ARTIFICIAL INTELLIGENCE AND LINGUISTICS: THE SYNERGY OF ENGLISH IN SCIENCE AND TECHNOLOGY - RAMADILLA, HAFIZA SAUMI; SURBAKTI, HALIMAH BR; NATSIR, MUHAMMAD (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
This article explores the role of artificial intelligence (AI) in strengthening English as a global lingua franca, particularly in the fields of science, technology, and education. Using a descriptive qualitative approach, the study examines how AI technologies, including Natural Language Processing (NLP) and Neural Machine Translation (NMT), facilitate cross-cultural communication and enhance language learning. AI-powered tools such as Google Translate, Grammarly, Duolingo, and Chatbots are prime examples of how these technologies increase accessibility, accuracy, and efficiency in mastering English. AI supports learners in overcoming linguistic barriers by providing real-time translation, grammar correction, and personalized learning experiences. The findings highlight the importance of developing AI in an ethical, inclusive, and responsible manner to ensure it not only strengthens English’s role as a global language but also preserves the world’s rich linguistic and cultural diversity. An interdisciplinary approach shows AI’s potential to foster equitable, sustainable, and inclusive communication worldwide. By balancing technological advancement with cultural preservation, AI can empower diverse communities, reduce language gaps, and support global collaboration. This research underscores the need for continuous innovation in AI while respecting cultural and linguistic identities to create a harmonious global communication environment. ABSTRAKArtikel ini membahas peran kecerdasan buatan (AI) dalam memperkuat bahasa Inggris sebagai lingua franca global, khususnya di bidang sains, teknologi, dan pendidikan. Dengan menggunakan pendekatan deskriptif kualitatif, studi ini meneliti bagaimana teknologi AI, seperti Natural Language Processing (NLP) dan Neural Machine Translation (NMT), memfasilitasi komunikasi lintas budaya dan meningkatkan pembelajaran bahasa. Alat berbasis AI seperti Google Translate, Grammarly, Duolingo, dan Chatbot menjadi contoh utama bagaimana teknologi ini meningkatkan aksesibilitas, akurasi, dan efisiensi dalam menguasai bahasa Inggris. AI membantu pembelajar mengatasi hambatan bahasa dengan menyediakan penerjemahan real-time, koreksi tata bahasa, serta pengalaman belajar yang dipersonalisasi. Hasil penelitian menekankan pentingnya pengembangan AI yang etis, inklusif, dan bertanggung jawab agar AI tidak hanya memperkuat peran bahasa Inggris sebagai bahasa global tetapi juga menjaga keragaman bahasa dan budaya di dunia. Pendekatan interdisipliner menunjukkan potensi AI dalam mendorong komunikasi yang adil, berkelanjutan, dan inklusif secara global. Dengan menyeimbangkan kemajuan teknologi dan pelestarian budaya, AI dapat memberdayakan berbagai komunitas, mengurangi kesenjangan bahasa, serta mendukung kolaborasi global. Penelitian ini menekankan perlunya inovasi berkelanjutan dalam AI sambil tetap menghormati identitas budaya dan bahasa untuk menciptakan lingkungan komunikasi global yang harmonis.